Human health risk, potentials of biomonitoring and phytoremediation of copper using Amaranthus viridis - Al-Mutairi, K.A.; Yap, C.K. (Corvinus University of Budapest, 2024)
This study aimed to determine copper (Cu) levels in Amaranthus viridis collected from 11 Peninsular Malaysia sampling sites and to estimate its human health risk. In addition, it also aims to assess the potential of A. viridis as a biomonitor and phytoremediator of Cu pollution. From a biomonitoring point of view, the Cu concentrations in the leaves, stems, and roots of A. viridis ranged from 10.8 to 21.9 µg/g dw (1.30-2.63 µg/g ww), 5.96 to 14.60 µg/g dw (0.36-0.88 µg/g ww), and 9.17 to 30.68 µg/g dw (1.01-3.37 µg/g ww), respectively. From the health risk aspect, it was found that the target hazard quotient (THQ) for Cu in the edible leaves of A. viridis were all below 1.00, indicating there were no non-carcinogenic risks of Cu to consumers, regarding both children and adults. Still, routine monitoring and managing the vegetable farms are recommended and necessary. From a phytoremediation perspective, with most bioconcentration factor values> 1.0 and the transfer factor> 1.0, A. viridis is a very potential phytoextraction agent of Cu. The experimental greenhouse study indicated that A. viridis could be a Cu biomonitor.